Dizocilpine (MK-801) impairs learning in the active place avoidance task but has no effect on the performance during task/context alternation - Vojtechova, Iveta; Petrasek, Tomas; Hatalova, Hana; Pistikova, Adela; Vales, Karel; Stuchlik, Ales (Behavioural brain research, 2016)
The prevention of engram interference, pattern separation, flexibility, cognitive coordination and spatial navigation are usually studied separately at the behavioral level. Impairment in executive functions is often observed in patients suffering from schizophrenia. We have designed a protocol for assessing these functions all together as behavioral separation. This protocol is based on alternated or sequential training in two tasks testing different hippocampal functions (the Morris water maze and active place avoidance), and alternated or sequential training in two similar environments of the active place avoidance task. In Experiment 1, we tested, in adult rats, whether the performance in two different spatial tasks was affected by their order in sequential learning, or by their day-to-day alternation. In Experiment 2, rats learned to solve the active place avoidance task in two environments either alternately or sequentially. We found that rats are able to acquire both tasks and to discriminate both similar contexts without obvious problems regardless of the order or the alternation. We used two groups of rats, controls and a rat model of psychosis induced by a subchronic intraperitoneal application of 0.08mg/kg of dizocilpine (MK-801), a non-competitive antagonist of NMDA receptors. Dizocilpine had no selective effect on parallel/sequential learning of tasks/contexts. However, it caused hyperlocomotion and a significant deficit in learning in the active place avoidance task regardless of the task alternation. Cognitive coordination tested by this task is probably more sensitive to dizocilpine than spatial orientation because no hyperactivity or learning impairment was observed in the Morris water maze.
Keywords: Analysis of Variance; Animals; Dizocilpine Maleate; Task alternation; Morris water maze; Excitatory Amino Acid Antagonists; reakční čas; Rats, Long-Evans; Avoidance Learning; Locomotion; poruchy učení; Learning Disabilities; Dizocilpine; lokomoce; analýza rozptylu; potkani Long-Evans; Male; dizocilpinmaleát; modely nemocí na zvířatech; Active place avoidance; učení vyhýbat se; Context alternation; Schizophrenia; Disease Models, Animal; krysa rodu Rattus; Reaction Time; Maze Learning; zvířata; mužské pohlaví; bludiště - učení; Rats; antagonisté excitačních aminokyselin